(untitled) (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation. People's wisdom in the form of proverbs and sayings in every nation lives and is passed on from generation to generation since the time when there was no written language. They include human observation of the surrounding world, actions of other people and warnings to the descendants. Sayings with numerals are no exception. Modern people, pronouncing famous statements, do not even think that they use the words of ancient folk wisdom in their speech. So firmly sayings and winged phrases entered our speech, as well as numbers. Numbers have entered our lives so long ago that we do not even pay attention to it. They surround us everywhere, but it's just information that conveys to our consciousness some kind of messages.